The DISAGREEMENT of IMAM ABU HANIFAH and His COMPANIONS to The COMPANIONS of IBN MAS’UD, The BOOK of FASTING is a MODEL - COMPRATIVE JURISPRUDENCE - Kareem , Ammar; Hamad, Yassin (Islamic Sciences Journal, 2023)
Praise be to Allah, Lord of the Worlds, and prayers and peace be upon our master Muhammad and his family and companions: After: The research in Islamic jurisprudence is renewed by the renewal of time and the renewal of facts and events to solve what the society is facing problems that occur over time and the jurisprudence of its flexibility and renewal by dissolving that contract by the diligence of the jurisprudents of the nation. The importance of this study lies in the statement that the disagreement between Abu Haneefah (may Allaah have mercy on him) and Ibn Mas'ud ( may Allah Pleased with him) was not in the matters of faith, but rather in the matters of diligence. It is consistent with the circle of thought . It also explains the clear face of the Islamic jurisprudence, which is characterized by a variety of opinions and divergent views and a statement that intolerance to doctrinal views is not the approach of our dear imams. The research plan was formed from the introduction: the importance of the topic and the choice of it : Ruling on fasting on the day of doubt, and the second requirement: Ruling on the day of doubt if the sight of the crescent before or after sunset is established.